Food biochemistry and food processing / Benjamin K Simpson ...[et al] - Nollet, Leo M. L. editor
Simpson (food science and agricultural chemistry, McGill U., Canada) brings together academics and industry professionals working in food biochemistry, processing, and safety around the world for this 45-chapter textbook aimed at food scientists, researchers and technologists in the food industry, and faculty and students in food science, technology, and engineering. It combines the areas of food biochemistry and food processing to help them rationalize and develop more effective strategies to produce and preserve food. It covers the essential principles of food biochemistry, enzymology, and food processing, then the biochemistry of meat, poultry, seafoods, milk, fruits, vegetables, cereals, and fermented foods, and food microbiology and safety. Along with updates to several chapters, this edition has been revised to incorporate safety considerations and the chemical changes induced by processing in the biomolecules of food in each chapter. It includes a new section on health and functional foods and 10 new chapters on topics like thermally and minimally processed foods, separation technology, and allergens